Analisis Yakuwarigo dalam Karakterisasi Tokoh Anime Katekyo Hitman Reborn! - Crystal Calista Katyusha Prasetya; Wiwik Retno Handayani (East Asian Review, 2026)
Yakuwarigo, or role language, is a type of virtual language used in Japanese fiction to reflect stereotypical character traits. This study discusses the use of yakuwarigo in the anime Katekyo Hitman Reborn! (KHR) with the aim of identifying the types, functions, and factors that influence the appearance of yakuwarigo in its characters. This study uses a qualitative method with data collection techniques in the form of listening and noting the dialogues of nine characters who are considered to represent yakuwarigo in the anime. Data analysis uses Kinsui's (2003) yakuwarigo theory, which classifies role language patterns based on linguistic and social stereotypes. The results of the study show that the types of yakuwarigo that appear can be classified into three main classifications, namely based on gender, based on era, and based on age. The functions of yakuwarigo found include four main domains, namely social identity function, relational function, emotional function, and narrative function. This study also found three factors that influence the use of yakuwarigo, namely social factors, historical factors, and characterisation factors. This study shows that yakuwarigo does not always strictly follow linguistic stereotypes, but rather functions flexibly according to the needs of characterisation and the context of the story.